2020
DOI: 10.3390/pr9010009
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Numerical and Multi-Objective Optimal Design of Wavy Plate-Fins Heat Exchangers

Abstract: This paper presents a method for optimizing wavy plate-fin heat exchangers accurately and efficiently. It combines CFD simulation, Radical Basis Functions (RBF) with multi-objective optimization to improve the performance. The optimization of the Colburn factor j and the friction coefficient f is regarded as a multi-objective optimization problem, due to the existence of two contradictory goals. The approximation model was obtained by Radical Basis Functions, and the shape of the heat exchanger was optimized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The standard k model was used for simulation calculation in order to obtain accurate simulation results. The average time domain of the Navier-Stokes equations to obtain the continuity and momentum equations for incompressible flow is as follows [18][19][20] (1) Other parameters in the standard k-ε model (Formulas ( 5) and ( 6)) are as follows: C μ = 0.09; C 1ε = 1.44, C 2ε = 1.92; C 3ε = tanh|v/u|; a 2 is the kinetic energy of sound propagation in a fluid; u and v are two mutually perpendicular velocity components.…”
Section: Geometric Model and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard k model was used for simulation calculation in order to obtain accurate simulation results. The average time domain of the Navier-Stokes equations to obtain the continuity and momentum equations for incompressible flow is as follows [18][19][20] (1) Other parameters in the standard k-ε model (Formulas ( 5) and ( 6)) are as follows: C μ = 0.09; C 1ε = 1.44, C 2ε = 1.92; C 3ε = tanh|v/u|; a 2 is the kinetic energy of sound propagation in a fluid; u and v are two mutually perpendicular velocity components.…”
Section: Geometric Model and Boundary Conditionsmentioning
confidence: 99%
“…The standard k model was used for simulation calculation in order to obtain accurate simulation results. The average time domain of the Navier–Stokes equations to obtain the continuity and momentum equations for incompressible flow is as follows [ 18 20 ]: …”
Section: Geometric Model and Boundary Conditionsmentioning
confidence: 99%
“…Khodabandeh E et al used the finite volume method and two-phase mixing model to simulate the turbulent flow and heat transfer of water silver nanofluid in a spiral heat exchanger with elliptic valves. The results showed that the flow and heat transfer characteristics depended on the height of the pillow, the concentration of nanoparticles and the Reynolds number [29]. Hwang et al [30] designed a plate heat exchanger (PHE) with a dimple-protrusion-patterned surface and conducted an experimental study on it.…”
Section: Introductionmentioning
confidence: 99%
“…Do Nascimento et al [16] combine a CFD simulation of fins with neural networks to optimize the pressure drop and heat transfer characteristics of fins in a two-stream PFHE. In a similar approach, Yu et al [17] use a CFD simulation with radical basis functions to employ the detailed simulation model of wavy fins in an optimization routine using a multi-objective genetic algorithm. Cui and Song [18] also focus on the heat transfer and pressure drop performance of wavy fins.…”
Section: Introductionmentioning
confidence: 99%